The effects of supplemental L-carnitine on growing performance of milkfed calves - Gorgulu, M.; Karakok, Serap Goncu; Gokce, G. (Cuban Journal of Agricultural Science, 2010)
Forty-nine Holstein male calves were allocated in three subgroups at 3 days of age. L-carnitine supplementation levels of 0 (control), 90, and 180 mg/d were assigned randomly to the subgroups. All calves were weaned at the 70th d, and consumed 268 L of whole milk (4 kg/calf daily) in two meals during the weaning period. They also had free access to alfalfa straw and calf grower after the first week. Supplemental L-carnitine (CARNIPASS containing 18 % L-carnitine is the trademark registered by Lonza Ltd., Switzerland) was given to the calves with the morning milk during the whole experimental period. L-carnitine supplementation did not have any effect on daily gain, concentrate, roughage and total feed intake, and feed to gain ratio of milk fed calves. There was, however, a decreasing tendency (380 g/day for control, 363 g/day for 90 mg group and 341 g/day for 180mg/day) in the daily gain of calves as the L-carnitine level increased. Additionally, L-carnitine supplementation increased incidence of diarrhea (one case for control and 5 and 4 cases for 90 and 180 mg/d supplementation, respectively) in calves. In conclusion, milk-fed calves may meet their carnitine requirement from given milk along with alfalfa straw and calf grower concentrate, and 90 and 180 mg/day L-carnitine supplementation may increase diarrhea incidence in milk-fed calves. Key words: calf, L-carnitine, health, growth, performance.